2012
DOI: 10.3892/ol.2012.694
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD133 in SW620 colorectal cancer cells is modulated by the microenvironment

Abstract: Abstract. The use of CD133 as a marker for identifying and isolating colon cancer stem cells (CSCs) is controversial. In particular, it is not clear whether the pattern of expression is influenced by the tumor microenvironment. We analysed the expression of CD133 in the SW620 colon cancer cell line, which produces subpopulations with different levels of CD133. CD133 neg and CD133 hi SW620 cells were isolated and compared in hanging drop spheroid cultures. The expression of CD133 was examined under different cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…They found that the frequency of tumor cells positive for stem cell-like cell markers and markers of more differentiated cells varied according to the tumor subtype and histologic stage [61]. Furthermore, a recent study found that CD133 expression in colorectal cancer cells is modulated by the microenvironment [62]. In addition to colorectal cancer, there are other cancers in which the expression of CD133 is regulated, such as gliomas and prostate cancer.…”
Section: Surface Markersmentioning
confidence: 99%
“…They found that the frequency of tumor cells positive for stem cell-like cell markers and markers of more differentiated cells varied according to the tumor subtype and histologic stage [61]. Furthermore, a recent study found that CD133 expression in colorectal cancer cells is modulated by the microenvironment [62]. In addition to colorectal cancer, there are other cancers in which the expression of CD133 is regulated, such as gliomas and prostate cancer.…”
Section: Surface Markersmentioning
confidence: 99%
“…In addition, hypoxia-induced CD133 expression has been reported in human lung cancer cell lines (12). It has been reported that in SW620 colorectal cancer cells, CD133 expression changes depending on the type of the microenvironment (25). Under the low-nutrient culture condition, CD133-negative SW620 colorectal cancer cells re-expressed CD133.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al first identified the presence of 1.3% to 13.6% of CD133 + cells in 35 individual HCC specimens by flow cytometry that generated tumors in SCID/Beige mice in serial transplantations [7]. CD133-positive population is generally in a relative constant percentage in cell lines and tissues but increased in malignant transformation, which suggest that the transmembrane pentaspan protein may play an essential role in cell metabolism and survival [8][10]. Characterizing CD133 functions in tumor and incorporating these findings into cancer drug discovery might lead to better therapeutic approaches [11].…”
Section: Introductionmentioning
confidence: 99%